2020
DOI: 10.1111/1755-6724.14529
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change, Geopolitics, and Human Settlements in the Hexi Corridor over the Last 5,000 Years

Abstract: Social responses to climate change over human history have been widely discussed in academia over the last two decades. However, the transformation of the human–environment nexus crossing prehistoric and historic periods and the processes associated with it are not yet clearly understood. In this study, based on published works on radiocarbon dating, archaeobotany, zooarchaeology, and archaeological sites, together with a synthesis of historical documents and high‐resolution paleoclimatic records, we trace the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Its wide range of ecological tolerance allows farmers to cultivate barley in very diverse environmental zones, from arid deserts to 4,500 masl (Knüpffer et al, 2003). Yet, change in environmental conditions induced by climate change may have had an important impact on agriculture development or caused farmers to move up or down in ecoclines (Hsu, 1998;Büntgen et al, 2011;Yang et al, 2020a). High-altitude ecosystems are highly sensitive to climate changes (Huang et al, 2014;Schwarz et al, 2017); thereby, the regional changes in precipitation and temperature patterns could directly affect the duration of the growing season or yields.…”
Section: Developmental Plasticitymentioning
confidence: 99%
“…Its wide range of ecological tolerance allows farmers to cultivate barley in very diverse environmental zones, from arid deserts to 4,500 masl (Knüpffer et al, 2003). Yet, change in environmental conditions induced by climate change may have had an important impact on agriculture development or caused farmers to move up or down in ecoclines (Hsu, 1998;Büntgen et al, 2011;Yang et al, 2020a). High-altitude ecosystems are highly sensitive to climate changes (Huang et al, 2014;Schwarz et al, 2017); thereby, the regional changes in precipitation and temperature patterns could directly affect the duration of the growing season or yields.…”
Section: Developmental Plasticitymentioning
confidence: 99%
“…59 Evidence from archeology depicts that between 3000 and 2200 BP, the intensity of human interaction and climate change transformed the original prehistoric economy into a pastoral economy. 57,59,60 At that time, the mild climate proved suitable condition for the development of agriculture. 61 For example, silk production and silkworm breeding evolved in the east and south of the country.…”
Section: Why Silk-color Entangled Terms Excelled More Than Other Object-color Entangled Termsmentioning
confidence: 99%
“…Among the studies of adaptive changes, the evaluation of the factors leading to significant changes in subsistence strategy in human prehistory and history is a fascinating topic. Climate change, technological innovation, rapidly growing population, trans-continental cultural exchange, human migration, and geopolitics are clear potential candidates ( Cohen, 1975 ; Bonsall et al, 2002 ; Gao et al, 2007 ; Pokharia et al, 2017 ; Cheung et al, 2019 ; Petraglia et al, 2020 ; Yang et al, 2020 ; Li et al, 2021 ). Climate change is well-studied and considered one of the most guiding factors of shifting subsistence strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The area was also a crossroads of agricultural and nomadic populations within China. Multiple lines of evidence showed that a significant shift in subsistence strategies along the Hexi Corridor occurred during the Han Dynasty ( Ma et al, 2016 ; Yang et al, 2019a ; Yang et al, 2020 ). Historical records from the Shiji (Records of the Grand Historian, 史记) to the Hanshu (Book of Han, 汉书) stated that the Hexi Corridor was occupied by nomadic pastoralists (Xiongnu, Yuezhi, and Wusun) before the Han Dynasty, a claim supported by excavated relics and faunal remains from Shajing culture (2,900–2,100 cal yr BP) and Shanma culture (2,700–2,100 cal yr BP) ( Yang et al, 2019b ) sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation